Founder's human capital, entry strategies and start-up size - Sandra Gottschalk; Kathrin Müller; Michaela Niefert (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper analyzes empirically the determinants of new born firms' initial size. As survival prospects of young firms tend to be linked to a firm's start-up size, a better understanding of the factors influencing start-up size is crucial. Most of the rare literature on initial firm size focuses on industry characteristics. We contribute to the understanding of the determinants of initial firm size by analyzing firm specific factors such as founders' human capital composition and entry strategies. We find that in addition to industry effects start-up size is considerably influenced by the human capital of firm founders. We distinguish between generic and specific human capital. Generic human capital refers to the general knowledge acquired through formal education and professional experience and usually coincides with a higher personal wealth. Specific human capital comprises competences that can be directly applied to the entrepreneurial job. For generic human capital we find that having a university degree has a positive influence on start-up size. The same applies for general working experience proxied by the founder's age. For the specific human capital components we find that successful entrepreneurial experience and managerial experience gained in dependent employment support a higher start-up size. Altogether, specific human capital tends to have a larger impact on initial size than generic human capital. Entry strategies are expected to have a crucial influence on start-up size, because objectives of market entry largely determine the resources a firm requires. We distinguish between different types of entry strategies. On the one hand, we look at entry strategies based on innovation. We measure innovation by a variable which indicates if a firm carries out continuous R&D. On the other hand, entry is classified according to the main motive of the founders for firm formation. We conclude that different motives are accompanied by diverse entry strategies. The four main groups of entry strategies are independency entrepreneurship, opportunity entrepreneurship, spin-out entrepreneurship and necessity entrepreneurship. The results indicate that firms conducting R&D continuously start larger than others when measuring initial employment in full-time equivalents. We do not observe a significant effect on start-up size measured in head counts. This suggests that R&D tasks are mostly carried out by fulltime employees and to a lesser extent by persons working part-time for the firm. Further, firms with entry strategies based on the exploitation of new market opportunities as well as spin-out entrepreneurship exhibit a higher initial size while start-ups established from necessity appear to start at a smaller scale.
Keywords: L11; L26; J24; 330; firm start-up size; human capital; firm foundation; Unternehmensgründung; Humankapital; Unternehmer; Betriebsgröße; Markteintritt; Deutschland